If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 + -2x = 16x + 23 Reorder the terms: 115 + -2x = 23 + 16x Solving 115 + -2x = 23 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 115 + -2x + -16x = 23 + 16x + -16x Combine like terms: -2x + -16x = -18x 115 + -18x = 23 + 16x + -16x Combine like terms: 16x + -16x = 0 115 + -18x = 23 + 0 115 + -18x = 23 Add '-115' to each side of the equation. 115 + -115 + -18x = 23 + -115 Combine like terms: 115 + -115 = 0 0 + -18x = 23 + -115 -18x = 23 + -115 Combine like terms: 23 + -115 = -92 -18x = -92 Divide each side by '-18'. x = 5.111111111 Simplifying x = 5.111111111
| -25=5(1-2x) | | x-1=3x+3 | | x-15=-20 | | x^3+8x^2+9x=0 | | 6y=-6x-6 | | 88-3x=10x+32 | | x*11+4=y | | 6x+7+91=6x | | x^2+3x-13=8x+1 | | 29=21-4x | | 2x+38=1-x-58 | | x*8+72=y | | x^2-9x+22=4 | | 2(x+7)-(x+1)=0 | | 3-2(2+x)=x+5 | | 10x-143=5x-13 | | (3x+4)=(5x-7) | | 12-8x=57-43x | | 7X*7X=5X | | -4x*3+8x=0 | | (2x-3)-(-x+6)= | | -31-4x=5-10 | | 2x^6+3= | | 30+7y=-2y-6 | | 3x+32+(-24x)=6+-36x-6+-16x | | 6(4x-y)+5= | | 14x+6x=20 | | 6x^3-13x^2+9x-2=0 | | 4x(2)=32 | | (5x-3)*(-2x-5)=0 | | (2x-3)(x)=54 | | 3a+2=a+8 |